PENGARUH KONSENTRASI PGPR (Plant Growth Promoting Rhizobacteria) DAN DOSIS PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL KEDELAI (Glycine max (L.) Merrill ) PADA TANAH ULTISOL DI BATAKAN - Jainah Jainah; Akhmad Rizali; Tuti Heiriyani (Agroekotek View, 2019)
PGPR is biological product which it has functions as growth improved, nutrition provided, pest control and it can be plant growth acceleration. Chicken manure is an organic fertilizer which it can improving soil fertility and it can be plant growth acceleration. Ultisols is a easier erosion soils, therefore it has less of an organic matter and nutrition. Soybean is one of foodstuff which always increasing of necessary year by year. The pupose of this research was knowing an interaction of the treatments and the best treatments of PGPR and chicken manure towards growth and yield of soybean which planted on ultisols soil of Batakan. This research was using Split Plot Design two factor of treatments. First factor is PGPR concentration (J) as the main of plot, it has 4 levels there is control (J0), 7,5 ml PGPR/l of water (J1), 15 ml PGPR/l of water (J2) and 22,5 ml PGPR/l of water (J3) and the second factor is chicken manure (H) as the sub plot, it has 3 levels there is control (H0), 10 t/ha-1 (60 g of soybean) (H1) and 20 t/ha-1 (120 g of soybean) (H2). This research showed all of variable has not interaction between PGPR and chicken manure. The best treatment of PGPR is on 15 ml/l of water concentration (J2) towards plant’s height and towards harvest age. While, on treatment of chicken manure 20 t/ha-1 (H2) is the best dosage of plant height, root nodus, pods of plant and 100 of seeds weight.